The Philosophy and Practice of Amulets in Tibetan Buddhist Tantra: Wearing, Analyzing, and Recognizing Your Way to Liberation - James Gentry (Journal of Contemplative Studies)
Buddhist amulets have been a topic of academic research for decades. But scholarly presuppositions that amulets have circulated primarily in popular Buddhist milieus, related only tangentially to the pursuits of elite practitioners, has limited our appreciation of how amulets have inflected philosophical and contemplative concerns. This article aims to challenge this lopsided perspective by showing how Buddhists in Tibet integrated analytic contemplation into the practice of writing down, wearing, and putting into practice short tantric scriptures that claim to liberate through wearing. The discussion argues that carving out a place for analysis in amulet-tantra use can be traced to the revelations of the thirteenth century visionary scholar Guru Chöwang’s commentarial glosses on the phrase “liberation-through-wearing.” This discussion contextualizes the change of emphasizing analysis in amulet-tantra practice as a transition between the earlier Heart Essence of Vimalamitra revelations and the later Heart Essence of the Ḍākinī revelations in response to ongoing criticisms of the Great Perfection. This article concludes that the Heart Essence of the Ḍākinī’s tantra-amulets drew from Guru Chöwang’s revelation to harmonize analytic inquiry with the earlier Vimalamitra dispensation in ways that blur the boundaries between embodied tantric practice and discursive philosophical inquiry. This blurring of boundaries has ramifications for how we study Buddhist Tantra and philosophy.